Cutaneous presentation of Double Hit Lymphoma - Yousef Khelfa MD, FACP; Yehuda Lebowicz MD (SAGE Publishing, 2016)
Diffuse large B-cell lymphoma (DLBCL) is the most common type of non-Hodgkin lymphoma (NHL), representing approximately 25% of diagnosed NHL. DLBCL is heterogeneous disease both clinically and genetically. The 3 most common chromosomal translocations in DLBCL involve the oncogenes BCL2, BCL6, and MYC. Double hit (DH) DLBCL is an aggressive form in which MYC rearrangement is associated with either BCL2 or BCL6 rearrangement. Patients typically present with a rapidly growing mass, often with B symptoms. Extranodal disease is often present. Though there is a paucity of prospective trials in this subtype, double hit lymphoma (DHL) has been linked to very poor outcomes when patients are treated with standard R-CHOP. There is, therefore, a lack of consensus regarding the standard treatment for DHL. Several retrospective analyses have been conducted to help guide treatment of this disease. These suggest that DA EPOCH-R may be the most promising regimen and that achievement of complete resolution predicts better long-term outcomes.